PENGARUH PENGGUNAAN METODE PAIKEM TERHADAP MINAT BELAJAR MATA PELAJARAN AL-QUR’AN HADITS SISWA KELAS VIII DI MTs AL-AMIN PALUR: SISWA KELAS VIII DI MTs AL-AMIN PALUR - Firdaus, Hevinna; Abdullah Khoir , Mulyanto; Faridatul Ulfah , Yetty (QATHRUNÂ, 2023)
The purpose of this study was to determine the effect of PAIKEM method on the learning interest of class VIII students at MTs Al-Amin Palur. This type of research is quantitative in which the research subject is MTs Al-Amin Palur. The independent variable (Variable X) of this research is the PAIKEM method, while the dependent variable (Variable Y) is learning interest. The research population was all VIII grade students at MTs Al-Amin Palur which amounted to 20 students, so the sample of this study was all of the total population. Researchers collected data using an instrument in the form of a questionnaire consisting of 30 items of statement questions. In testing the validity, researchers used the product moment validity test and testing the reliability of researchers using the alpha cronbanch reliability test, in addition to using a questionnaire, researchers also used the documentation study method in data collection. The results showed that there was an influence between PAIKEM methods on the learning interest of VIII grade students at MTs Al-Amin Palur. Judging from the test results using product moment, the value of r count is 0.803 and the value of r table is 0.444. This means that r count> r table. So H0 is rejected so that there is a significant influence of PAIKEM method on the interest in learning of class VIII students at MTs Al-Amin Palur.